2020
DOI: 10.1101/2020.10.26.20219725
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Declining prevalence of antibody positivity to SARS-CoV-2: a community study of 365,000 adults

Abstract: Background The prevalence and persistence of antibodies following a peak SARS-CoV-2 infection provides insights into its spread in the community, the likelihood of reinfection and potential for some level of population immunity. Methods Prevalence of antibody positivity in England, UK (REACT2) with three cross-sectional surveys between late June and September 2020. 365104 adults used a self-administered lateral flow immunoassay (LFIA) test for IgG. A laboratory comparison of LFIA results to neutralization a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
174
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(188 citation statements)
references
References 27 publications
12
174
1
1
Order By: Relevance
“…Vaccine efficacies to protect against infection above 80% are desirable, 1 but duration of protection will remain uncertain for a number of years post licensure of COVID-19 vaccines. Preliminary evidence suggests waning antibody titres in those who have recovered from SARS-CoV-2 infection, 2 but antibodies are only one part of the human immune response and acquired immunity to reinfection or the prevention of disease when reinfected. 3 , 4 , 5 Data on immunity to other coronaviruses suggest that immunity to SARS-CoV-2 might be short lived, perhaps 12–18 months in duration.…”
mentioning
confidence: 99%
“…Vaccine efficacies to protect against infection above 80% are desirable, 1 but duration of protection will remain uncertain for a number of years post licensure of COVID-19 vaccines. Preliminary evidence suggests waning antibody titres in those who have recovered from SARS-CoV-2 infection, 2 but antibodies are only one part of the human immune response and acquired immunity to reinfection or the prevention of disease when reinfected. 3 , 4 , 5 Data on immunity to other coronaviruses suggest that immunity to SARS-CoV-2 might be short lived, perhaps 12–18 months in duration.…”
mentioning
confidence: 99%
“…134 A large-scale community study of 365 000 adults in the United Kingdom found a significant decline in the proportion of the population with detectable antibodies over three-rounds of testing 12, 18, and 24 weeks following the peak of COVID-19 cases. 135 The results of this study suggest that antibody-immunity against SARS-CoV-2 may be waning within the first 6-12 months. However, it is important to note that as this large-scale study was conducted via participants self-pricking and reporting, the results remain to be verified via further investigation.…”
Section: Adaptive Immune Responsementioning
confidence: 65%
“…In the population aged 75+ years, the drop was 39%. These data suggest that the possibility of decreasing population immunity over time could increase the risk of reinfection ( Ward et al, 2020 ). Currently the importance of antibody decline for reinfection by SARS-CoV-2 is not yet answered and further longitudinal studies are needed.…”
Section: Resultsmentioning
confidence: 96%